G. V. Ivanov’s Essays Across Europe by Car: The Image of Germany in the 1930s - Nina Vladimirovna Barkovskaya (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2022)
G. Ivanov’s essays Across Europe by Car describing the circumstances of the author’s real trip from Riga to Paris have signs of the genre of travel notes or travelogue. The theoretical basis the author uses to study Ivanov’s essays is the idea of the travelogue as a synthetic genre existing in a variety of forms. In the essays the article examines, travel turns into a political pamphlet. The essays meticulously reproduce the itinerary, place names, peculiarities of the way of life, architecture, and everyday details. However, the main content of the cycle focuses on Germany in the 1930s seized by the ideology of fascism. The caricature nature of the sketches borders on grotesque. Not only the leaders of Germany, but also Russian fascists (Bermondt-Avalov, Vonsyatsky, Pelhau) are depicted satirically. Describing the history of the Russian National Liberation Movement, a fascist union of Russian emigrants, Ivanov shows the reasons that attracted poverty-stricken emigrants to the organisation: the union promised protection to its members, gave them the illusion of a common cause, and seduced them with the hope of returning to Russia. The position of the author himself is quite unambiguous — he hates fascism which turns people into an obedient crowd, hypnotised by the speeches of the leaders. Sketches about Germany are framed by sketches about border towns and villages: the narrator enters through Lithuanian Šiauliai, and the description of the journey ends with his arrival at a border post in France. The beginning and the end of the essay cycle echo each other: on both sides, there are visible traces of the previous war, and the two places share a somewhat disordered but charming everyday life which is described with good humour. The main character is happy to leave Germany. However, the nation engulfed in the propaganda of its own greatness, full of belligerence already casts a shadow of threat on the neighbouring countries. At the same time, the old story of Duke Biron recounted in the essays indirectly expresses the author’s hope that every almighty despot will have to pay for his atrocities sooner or later.